POTENTIAL OF ILMENITE AS A SOLAR ABSORBER - Sousa, G. C. P.; Gomes, K. C.; Júnior, W. F. A.; Duarte, R. N. C. (Revista de Engenharia Térmica, 2020)
Titanium is considered the fourth most widely used material in industry worldwide. Titanium minerals are currently being applied in various branches of industry, mainly in the field of pigmentation. Ilmenite (FeTiO3) is an iron and titanium oxide of more common and abundant occurrence, with theoretical composition of Fe (36.8%), Ti (31.6%) and O (31.6%). Having regard to the potential of titanium minerals and the abundance of ilmenite, together with the importance of validating direct applications of this ore, since the processing of titanium is still complex and expensive, it is necessary to study this mineral and the knowledge of its main characteristics. This work brings thermal, chemical and mineralogical characterizations of ilmenite, in order to know the potential of application of this ore as a solar absorbing material. The characterization techniques used were: X-ray diffraction (XRD) and Rietveld refinement for phase quantification, X-ray fluorescence (XRF), optical spectroscopy in the middle infrared region with Fourier Transformation by Transmittance (FTIR) and thermogravimetric thermal analysis (TGA). The analyzed sample obtained X-ray diffractogram, ilmenite (80.6%) and rutile (19.4%) as significant phases, corroborating the FRX results that indicated greater presence of Fe and titanium oxide in the ilmenite chemical composition under study. The TGA, DTA and DSC analyses indicated good thermal stability of the material in medium and high temperatures. The integration of the obtained data shows that the application of this ore as a precursor material of absorber films for selective purposes is considerable.